2019
DOI: 10.1002/micr.30446
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the use of internal mammary artery perforators as a recipient vessel in free tissue transfer: An anatomical analysis by computed tomography angiography in breast cancer patients

Abstract: Background: The internal mammary artery (IMA) perforator has assumed recent prominence as recipient vessels in free autologous breast reconstruction. However, anatomical understanding is unclear, due to limited cadaver and clinical studies. We evaluated the usability of these vessels by evaluating perforator size, dominance, laterality, interspace location, and relationship with breast volume.Methods: A retrospective review assessed 197 female patients with breast cancer who had undergone computed tomography a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…However, several anatomical studies have demonstrated a relatively reliable IMAP anatomy. 8 , 9 The patient’s suitability for miraDIEP reconstruction was determined preoperatively using duplex ultrasound. The incision to closure time was longer compared with robot-assisted DIEPs with anastomoses directly to the IMA, although the time for anastomosis was not longer.…”
Section: Discussionmentioning
confidence: 99%
“…However, several anatomical studies have demonstrated a relatively reliable IMAP anatomy. 8 , 9 The patient’s suitability for miraDIEP reconstruction was determined preoperatively using duplex ultrasound. The incision to closure time was longer compared with robot-assisted DIEPs with anastomoses directly to the IMA, although the time for anastomosis was not longer.…”
Section: Discussionmentioning
confidence: 99%
“…The rectus abdominis muscle or local perforator flaps were considered because this have been reported in the literature recently 12 18. However, it also was deficient in volume for this patient, and the pedicle was unreliable because the extensive resection included the internal mammary artery and the eighth intercostal perforator 19. In addition, the omentum flap would not provide a stable construct.…”
Section: Discussionmentioning
confidence: 99%